Cognitive and Neural Development of Individuated Self-Representation in Children - Ray, Rebecca D. (2009)
Processing the self-relevance of information facilitates recall. Similarly, processing close-other-related information facilitates recall to a lesser degree than processing self-relevant information. This memory advantage may be viewed as an index of the degree to which the representation of self is differentiated from representations of close others. To test developmental hypotheses concerning the development of self, we examined the relation of memory for self- and mother- referentially processed information in participants age 7–13. Memory for words encoded with reference to oneself increases with age, relative to memory for words encoded with reference to one’s mother. When used as an individual difference measure, the difference in self versus mother memory correlates with regions of the rACC associated with affective salience.